2020
DOI: 10.3390/molecules25010199
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extraction of Extracted Oil from Pistacia lentiscus L.: Mathematical Modeling, Economic Evaluation and Scale-Up

Abstract: In this study, the extracted oil of Pistacia lentiscus L. the Tunis region was extracted using supercritical carbon dioxide (SC-CO2) extraction containing different major components in the oil such as α-pinene (32%) and terpinene-4-ol (13%). The investigation of the effect of different variables on the extraction yield with 5% level of confidence interval showed that the CO2 pressure was the main significant variable to influence the oil yield. In order to better understand the phenomena, three parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…According to Aydi et al. [ 17 ] the yield of Tunisian Pistacia lentiscus leaf oil using the supercritical CO 2 extraction technique varied between 0.093% and 0.285%. It is well known that the quantity of the yield from supercritical CO 2 extraction is affected by several operating conditions such as the CO 2 pressure, CO 2 mass flow rate, time of extraction, and average particle size.…”
Section: Resultsmentioning
confidence: 99%
“…According to Aydi et al. [ 17 ] the yield of Tunisian Pistacia lentiscus leaf oil using the supercritical CO 2 extraction technique varied between 0.093% and 0.285%. It is well known that the quantity of the yield from supercritical CO 2 extraction is affected by several operating conditions such as the CO 2 pressure, CO 2 mass flow rate, time of extraction, and average particle size.…”
Section: Resultsmentioning
confidence: 99%
“…[158] Aydi et al reported that the lowest production costs for Pistacia lentiscus oil extracted using SC-CO 2 were obtained at the higher volume of production. [159] Johner and team calculated the payback time to be shorter than one year, for pequi oil using SC-CO 2. This is interesting in terms of rapid recovery of initial investment.…”
Section: Supercritical Carbon Dioxide Extraction: Economic Feasibilit...mentioning
confidence: 99%
“…SCE uses supercritical carbon dioxide generated at critical conditions of 38 °C and 73.8 bar to extract a wide range of bioactive compounds, with the ability to preserve thermolabile compounds which can undergo degradation at high temperatures, since intensive heating is not required in this method (Nejad‐Sadeghi et al ., 2015). The carbon dioxide pressure, carbon dioxide mass flow rate, extraction time and particle size are considered four vital variables affecting the efficiency of SCE (Aydi et al ., 2020).…”
Section: Supercritical Carbon Dioxide Extractionmentioning
confidence: 99%